Програмна система візуальної підтримки проектування баз даних для nosql-системи Neo4j - Сиволовський, І. М. (ХНУРЕ, 2020)
The given work is devoted to the Neo4j database design system with visual modeling tools. The system is designed to simplify the design of Neo4j databases by providing CASE and code generation tools. The implemented system has the following functions: automatic generation of database schema according to ER diagram, creation of database queries with the help of a visual editor, generation of query code in different query languages, automatic creation of indexes for query optimization.